Existence and Iteration of Positive Solutions for One-Dimensional p-Laplacian Boundary Value Problems with Dependence on the First-Order Derivative. (2nd May 2008) - Wang, Zhiyong; Zhang, Jihui
Abstract : This paper deals with the existence and iteration of positive solutions for the following one-dimensionalp -Laplacian boundary value problems:( ϕ p ( u ′ ( t ) ) ) ′ + a ( t ) f ( t, u ( t ), u ′ ( t ) ) = 0, t ∈ ( 0, 1 ), subject to some boundary conditions. By making use of monotone iterative technique, not only we obtain the existence of positive solutions for the problems, but also we establish iterative schemes for approximating the solutions.